Acurácia da ultrassonografia com Doppler colorido na identificação de doença maligna em neoplasias foliculares da tireóide - Iared, Wagner [UNIFESP] (2010)
Background. In most cases it is possible to differentiate between benign and malignant thyroid nodules through cytologic analysis of the fine-needle aspiration biopsy (FNAB) samples. However, in the case of follicular neoplasms (FNs), to determine whether such nodules are benign or malignant, it is necessary to perform a surgical biopsy, which requires the removal of at least part of the thyroid gland. There are clues in the literature that the parameters of color Doppler ultrasonography (CDU) may indicate a greater or lesser likelihood of malignancy in these nodules. Objective. The purpose of this systematic review was to obtain summary estimates of the diagnostic accuracy of CDU in predicting malignancy in thyroid FNs. Methods. We searched Medical Subject Headings together with the search terms “follicular,” “thyroid,” and “Doppler” in the MEDLINE, Web of Science, Cochrane Library and Excerpta Medica databases as well as the Latin American and Caribbean Health Sciences Literature database, after which we performed manual searches of the reference lists to locate additional studies. There were no language restrictions. We included studies that assessed the diagnostic accuracy of CDU in identifying malignancy in thyroid FNs. The assessments of the quality and extraction of data were performed by 2 independent reviewers. Results. We included 4 studies, which collectively evaluated 457 thyroid FNs, 67 of which had been classified as malignant based on the evaluation of surgical biopsy samples. Moderate, rich, predominant, or exclusive internal flow on CDU of thyroid FNs was considered indicative of malignancy. The overall sensitivity of CDU was 85% (95% confidence interval [CI], 74%–93%), with an overall specificity of 86% (95% CI, 82%–89%). The overall prevalence was 14.7%, and the positive and negative predictive values were 51% and 97%, respectively. The positive likelihood ratio was 6.07, and the negative likelihood ratio was 0.18. Conclusion. CDU has good accuracy for identifying malignancy in thyroid FN. Predominant internal flow seen on CDU is associated with malignancy of thyroid FN.